2001
DOI: 10.1080/0142150020031084
|View full text |Cite
|
Sign up to set email alerts
|

Measuring effectiveness for best evidence medical education: a discussion

Abstract: This paper considers how educational interventions should be evaluated for their effectiveness. Five levels of effectiveness are clarified and illustrated: outcomes, behaviour, learning, reaction and participation. These levels are then discussed, within the context of research evidence for education within the medical profession. Methodological and practical research conclusions are then drawn. From an analysis of over 300 abstracts the evidence shows that only limited research on healthcare outcomes has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 25 publications
1
92
0
1
Order By: Relevance
“…Belfield et al (2001) found little exploration in the literature about the relationship between educational interventions and physician performance and patient outcomes (Belfield et al, 2001). Similarly, Mazmanian and Davis (2002) called for more research in the area of learning outcomes for physicians including how CME programs change clinical practice.…”
Section: Continuing Medical Educationmentioning
confidence: 99%
“…Belfield et al (2001) found little exploration in the literature about the relationship between educational interventions and physician performance and patient outcomes (Belfield et al, 2001). Similarly, Mazmanian and Davis (2002) called for more research in the area of learning outcomes for physicians including how CME programs change clinical practice.…”
Section: Continuing Medical Educationmentioning
confidence: 99%
“…This comprises four successive levels of outcome, ranging from simple reactions (i.e., supervisees' satisfaction with their supervision), to impacts on a service system (including the acid test). This taxonomy has latterly been augmented by Kraiger et al (1993), Alliger et al (1997) and Belfield et al (2001). As a result, changes in knowledge, skills, and attitudes as a result of learning have been added.…”
Section: Enactment Of Supervision 7 Conduct Stepwise Evaluationsmentioning
confidence: 99%
“…In the staff development literature this mini-outcome has been recognised as commencing with attendance, followed by "participation or completion" (Belfield, Thomas, Bullock et al, 2001). We should be particularly interested in active ingredients or change mechanisms, such as experiential learning, as these improve our understanding and effectiveness (Campbell et al, 2007).…”
Section: Receipt Of Supervision 6 Evaluate Mediators and Mechanismsmentioning
confidence: 99%
“…22 It is essential that dental academics use evidence from health and higher education research to inform curricular designs and educational approaches, particularly given that the quality of care that our dental graduates provide and subsequent patient health outcomes are likely to be related to their education. 23,24 Similarly, it is critical that we produce our own evidence regarding effective educational approaches that support student learning specific to dentistry, 25 as our contexts differ from other healthcare professions. For example, the extent of patient care provided by our students differs from the care provided by medical students.…”
Section: Where Are We Now?mentioning
confidence: 99%